Correlation between Physical Literacy and Academic Performance among Intermediate-Level Students at GHSS Daraban Khurd, Dera Ismail Khan: An Analysis Using Standardized Test Scores - LUQMAN, MUHAMMAD SAFDAR; MEHREEN, SADIA; RAZZAQ, FOUZIA ABDUL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Physical literacy (PL), which includes motivation, confidence, physical competence, and knowledge, supports lifelong physical activity and has been associated with cognitive benefits that may enhance academic achievement. Objective: This study examined the relationship between physical literacy and academic performance among male intermediate-level students in a rural boys’ school in Pakistan. Methods: A quantitative correlational design was used involving 126 male students aged 16–18 years from Government Higher Secondary School (GHSS) Daraban Khurd, Dera Ismail Khan. Academic achievement was assessed through matriculation results from the Board of Intermediate and Secondary Education (BISE) Dera Ismail Khan. Physical literacy was measured using the nine-item Perceived Physical Literacy Instrument (PPLI). Reliability of the instrument was evaluated via Cronbach’s alpha. Results: A significant positive correlation was found between physical literacy and academic performance (r = 0.34, p < 0.001). The PPLI demonstrated good internal consistency (Cronbach’s α = 0.79). Conclusion: Enhancing physical literacy may contribute to improved academic outcomes in resource-limited rural settings. Promoting physical education and accessible sports like cricket and kabaddi could foster academic success and overall wellbeing among rural schoolboys in Pakistan. Further longitudinal research is warranted to explore causal links.